Factors associated with treatment delay in women with primary breast cancer who were referred to reproductive specialists. Issue 2 (5th March 2019) - Kitano, Atsuko; Shimizu, Chikako; Yamauchi, Hideko; Akitani, Fumi; Shiota, Kyoko; Miyoshi, Yoko; Ohde, Sachiko
Abstract : Purpose: Cancer treatment delay due to fertility preservation procedures is a barrier for patients with breast cancer who wish to preserve their fertility. This study aimed to describe the associations between fertility preservation and treatment delay in patients with breast cancer with reproductive concerns and assess the factors related to treatment delay. Methods: Patients with primary breast cancer who visited the reproductive unit at our institution before cancer treatment between 2007 and 2015 were enrolled. The treatment delay cut-off was defined as follows: time to chemotherapy (TTC) >8 weeks for patients intending to receive neoadjuvant chemotherapy, TTC >12 weeks for patients intending to receive adjuvant chemotherapy, time to endocrine therapy (TTE) >12 weeks for patients intending to receive endocrine therapy without radiation therapy and TTE >20 weeks for patients intending to receive endocrine therapy after radiation therapy. Multivariable models were constructed to examine the factors of treatment delay. Results: Overall, 212 patients met the inclusion criteria. Using the defined cut-offs, treatment delay was noted in 18% of the patients. Endocrine therapy was related to treatment delay (OR 4.49, 95% CI 1.02 to 19.7; p=0.05), but fertility preservation by artificial reproductive treatment (ART) was not. Pregnancy and delivery following treatment for breast cancer were achieved in 18 (19%) and 15 (16%) patients who underwent fertility preservation with ART. Conclusion: Fertility preservation with ART was not associated with treatment delay in patients with breast cancer who were referred to reproductive specialists before cancer treatment.